2018
DOI: 10.1242/jcs.213967
|View full text |Cite
|
Sign up to set email alerts
|

IL1β and TNFα promote RANKL-dependent adseverin expression and osteoclastogenesis

Abstract: Adseverin is an actin-binding protein involved in osteoclastogenesis, but its role in inflammation-induced bone loss is not well-defined. Here, we examined whether IL1β and TNFα regulate adseverin expression to control osteoclastogenesis in mouse primary monocytes and RAW264.7 cells. Adseverin was colocalized with subcortical actin filaments and was enriched in the fusopods of fusing cells. In precursor cells, adseverin overexpression boosted the formation of RANKL-induced multinucleated cells. Both IL1β and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…In addition to the effects on BMSC senescence and osteogenesis, the upregulation of SASP inflammatory factors may also promote osteoclastogenesis. For example, IL1, IL6, IL8, and MCSF contribute to osteoclast formation and activity (Briot et al 2017, Wang et al 2018. In our experiments, osteoclastogenesis enhancement in OVX mice was confirmed, and the in vivo injection of a JAK inhibitor reduced the number of osteoclasts on the bone surface (Supplementary Fig.…”
Section: Journal Of Endocrinologysupporting
confidence: 65%
“…In addition to the effects on BMSC senescence and osteogenesis, the upregulation of SASP inflammatory factors may also promote osteoclastogenesis. For example, IL1, IL6, IL8, and MCSF contribute to osteoclast formation and activity (Briot et al 2017, Wang et al 2018. In our experiments, osteoclastogenesis enhancement in OVX mice was confirmed, and the in vivo injection of a JAK inhibitor reduced the number of osteoclasts on the bone surface (Supplementary Fig.…”
Section: Journal Of Endocrinologysupporting
confidence: 65%
“…Hence, defects in the migration of precursors results in a decreased OCL fusion. These molecules include Rac2 [ 86 ], adseverin [ 126 ], and LIM1 [ 127 ]. A force-generating molecule, Myosin X, is known to be also involved in the migration of the precursors [ 128 ].…”
Section: Multiple Roles Of the Actin Cytoskeleton In Phagocyte Mulmentioning
confidence: 99%
“…Previous published studies have revealed that although IL-1 can activate osteoclast maturation and enhance bone resorption, it alone cannot initiate the process of osteoclast differentiation from osteoclast precursors (18,19). Kim et al (20) however, suggested that IL-1 can induce osteoclast differentiation without the interaction of RANKL/RANK in the context of appropriate microenvironmental conditions.…”
Section: Introductionmentioning
confidence: 99%